ANALISIS PENGELOLAAN SAMPAH DENGAN PRINSIP 3R (Reduce, Reuse, Recycle) (Studi Kasus Di Desa Mamak Kabupaten Sumbawa) - Junaidi, Junaidi; Utama, Abdul Alimun (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Waste is the result of human activities in rural areas that exert great pressure on the environment, especially with the state of waste not being collected and eventually accumulating in open places and bodies of water. Waste management in general can be done by burning, throwing into sewers, piling up around houses and most often thrown into rivers. Although some experts have found various ways to deal with waste, including how to recycle, these methods still do not solve the problem of waste that is increasing in quantity and type, both in rural areas and in other settlements. One of the programs for handling waste problems is through the 3R program where the program is a program by implementing the 3R principle, namely reducing or reducing the amount of waste, recycling or recycling waste, and reuse or reuse waste. This research method is to use qualitative and quantitative methods. The problem in this study is how the picture and condition of waste management in Mamak Village, Sumbawa Regency, waste management planning with the 3R principle. Data collection using primary data was obtained through calculations of waste generation, questionnaires / interviews with the people of Mamak Village. The samples in this study were calculated to obtain as many as 30 samples obtained from Mamak Village, Sumbawa Regency. The results of this research in Mamak Village in particular have not been maximized in applying the 3R concept so that TPST planning is needed, therefore in applying the 3R principle, it is necessary to have the participation of the government to further improve the application of the 3R principle.